A new Korean earthworm (Oligochaeta: Megadrilacea: Megascolecidae) - Blakemore, Robert J.; Park, Tae Seo; Seo, Hong-Yul (Zootaxa, 2012)
Amynthas gageodo Blakemore, sp. nov. is described from small Gageo-do Island, offshore to the southwest of the Korean Peninsula in the Yellow Sea. It is an octothecal species (four pairs of spermathecae) comparable to Japanese Amynthas carnosus (Goto & Hatai, 1899) (synonyms: Korean kyamikia Kobayashi, 1934, monstrifera Kobayashi, 1936, sangyeoli Hong & James, 2001, youngtai Hong & James, 2001, kimhaeiensis Hong & James, 2001, sinsiensis Hong & James, 2001, baemsagolensis Hong & James, 2001, Taiwanese monsoonus James et al., 2005) and to Chinese A. pingi (Stephenson, 1925) (synonym: fornicata Gates, 1935). Species associations in its forest litter habitat on the remote island included terrestrial leeches, planarian flatworm predators and other worms. MtDNA COI barcodes indisputably identify types of A. gageodo as a new model for future Korean earthworm species characterizations.